2021
DOI: 10.2174/1389450121999201230203709
|View full text |Cite
|
Sign up to set email alerts
|

Insight γ-Secretase: Structure, Function, and Role in Alzheimer’s Disease

Abstract: Abstract:: Neurodegenerative disorders are the state of body results in progressive degeneration leading to death of nerve cells. In this state, a patient gets affected day by day with mental weakness, dementia and ataxia. Alzheimer’s disease (AD) is the most common irreversible neurodegenerative brain disorder mainly affecting people over the age of 65 years. Many researches suggest a fact that the main culprit for AD is the aggregated form of a (39-43) amino acid peptide called amyloid beta. Amyloid beta (Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In the light of our findings and the supporting documentations ( 16 , 39 41 ), we propose a model for PSEN1 to regulate tumor-immune interactions via influencing PD-L1 nuclear translocation ( Figure 3 ). In this model, the upregulated PSEN1 in colon cancer facilitates PD-L1 truncation via potential proteolytic processing, releasing its active C-terminal fragment, and then induces PD-L1 nuclear translocation through impacts on the multiple components in HDAC2-mediated deacetylation, clathrin-dependent endocytosis, vimentin-associated nucleocytoplasmic shuttling and importin family-mediated nuclear import.…”
Section: Resultssupporting
confidence: 57%
“…In the light of our findings and the supporting documentations ( 16 , 39 41 ), we propose a model for PSEN1 to regulate tumor-immune interactions via influencing PD-L1 nuclear translocation ( Figure 3 ). In this model, the upregulated PSEN1 in colon cancer facilitates PD-L1 truncation via potential proteolytic processing, releasing its active C-terminal fragment, and then induces PD-L1 nuclear translocation through impacts on the multiple components in HDAC2-mediated deacetylation, clathrin-dependent endocytosis, vimentin-associated nucleocytoplasmic shuttling and importin family-mediated nuclear import.…”
Section: Resultssupporting
confidence: 57%
“…46 γ-Secretase is a transmembrane protein complex that mediates the final cleavage of APP which eventually liberates Aβ. 47 γ-Secretase inhibitors were shown to be a potential approach for treating Alzheimer's, 4 but there are worries about their deleterious side effects, namely, worsening of the cognitive, functional, and clinical performances. 48 In ophthalmology, a recent study on rats concluded that γ-Secretase inhibitors might provide a therapeutic approach in prevention and treatment of subretinal fibrosis in neovascular AMD and other fibrovascular diseases.…”
Section: High Yield Medical Reviewsmentioning
confidence: 99%